2019
DOI: 10.3390/agronomy9090544
|View full text |Cite
|
Sign up to set email alerts
|

Killing Weed Seeds with Exhaust Gas from a Combine Harvester

Abstract: We investigated if hot exhaust gas from a combine harvester could be used to reduce germination or kill weed seeds during the harvesting process. During the threshing and cleaning process in the combine, weed seeds and chaff are separated from the crop grains. After this separation, weed and crop seeds not collected can be exposed to exhaust gas before seeds are returned to the field. Seeds of some common weed species (Alopecurus myosuroides, Centaurea cyanus, Geranium pusillum, Lapsana communis, Lolium perenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…P. rhoeas and V. arvensis were the most sensitive species, both having small seeds, while C. cyanus and E. cicutarium were the least sensitive having the largest seeds (Tables 1 and 3, Figures 2-4). Jakobsen et al [12] also found that C. cyanus were less sensitive to a short pulse of heat than the other tested species with smaller seed weight. Large seeds might be more protected against a pulse of high temperature because it takes a longer time to distribute the heat in a large seed than in a small one [22].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…P. rhoeas and V. arvensis were the most sensitive species, both having small seeds, while C. cyanus and E. cicutarium were the least sensitive having the largest seeds (Tables 1 and 3, Figures 2-4). Jakobsen et al [12] also found that C. cyanus were less sensitive to a short pulse of heat than the other tested species with smaller seed weight. Large seeds might be more protected against a pulse of high temperature because it takes a longer time to distribute the heat in a large seed than in a small one [22].…”
Section: Discussionmentioning
confidence: 91%
“…Jakobsen et al [12] investigated whether exhaust gas from a combine harvester could be used to kill weed seeds. The idea was to explore the potential to develop a system implemented in the combine harvester that could expose the chaff and weed seeds to the large air pressure and waste heat energy from the exhaust gas before the material was returned to the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have now shown that a large proportion of seeds produced during the growing season of common weed species potentially can be collected and removed or destroyed [43][44][45] by a combine harvester at crop harvest. The next step will be to test how large a fraction of this potential a combine harvest actually collects, as it depends on several factors such as harvest height and the number of seeds dropping to the soil surface under the harvesting process.…”
Section: Discussionmentioning
confidence: 99%
“…If the moisture content of the harvested material is high, the temperature may not be high enough to heat the seeds until the core reached 80 • C. Too high moisture contents would lead only to surface evaporation without affecting the germination ability of the weed seeds. However, a temperature of 75−85 • C may release the dormancy of some weed species [39] and make them sensitive to weed control before the new crop emerged instead of being incorporated into the soil seed bank. Long-term surveys are necessary to evaluate the impact of weed seed harvest control on the soil seed bank of the different weed species.…”
Section: Thermal Treatment Of Seedsmentioning
confidence: 99%